Pengaruh Konsumsi Olahan Jantung Pisang terhadap Peningkatan Produksi Air Susu Ibu pada Ibu Postpartum - Ruri Yuni Astari; Vika Hardianti (Universitas Faletehan, 2022)
Banana flower is well-known as an ingredient of traditional food and proved to increase breast milk production. However, the benefits of banana flower are not widely known by Indonesian people, especially to increase breast milk production. This study aimed to determine the effects of consuming processed banana flower on the increase of breast milk production among postpartum mothers. This study used pre-experimental analytical quantitative method with one group pretest posttest approach. The samples were 20 postpartum mothers on days 3-14, who were taken by using a purposive sampling technique. The univariate data analysis used central tendency distribution and the bivariate analysis used paired sample t-test. The results showed that the mean of breast milk production before consuming processed banana flower was 81.50 and after consuming processed banana flower was increased to 99.55 with a difference of 18.05 per minute. The results of statistical tests obtained a p value of 0.000 (α<0.05) which means that there was effect of consuming processed banana flower on the increase of breast milk production. Health officers need to know the benefits of consuming processed banana flower and educate postpartum mothers to cook banana flower and consume it during breastfeeding period to increase their breast milk production.